2019
DOI: 10.2147/ott.s194549
|View full text |Cite
|
Sign up to set email alerts
|

<p>Increased <em>MCL-1</em> expression predicts poor prognosis and disease recurrence in acute myeloid leukemia</p>

Abstract: Background: Altered expression of the BCL-2 family member MCL-1 has been linked to the progression and outcome of various malignancies. Recently, MCL-1 inhibitor S63845 was reported to kill MCL-1 -dependent cancer cells and has potential value in clinical application. Purpose: Herein, we reported MCL-1 expression pattern in Chinese de novo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
(50 reference statements)
1
26
0
1
Order By: Relevance
“…However, El-Halawani et al, (2017) reported high level of miRNA29a expression in Flt3-ITD+ as compared to the Flt3-ITD. Moreover, the correlation analysis revealed the presence of significant positive direct association between levels of mir-29a and mir-92a (r=0.533, p = 0.001) and negative correlation with MCL1 transcript level was observed (r= -0.606, p<0.001, r= -0.339, p=0.043, respectively) and this was consistent with other studies that showed that down-regulation of miR-29a and miR-29b accompanied by up-regulation of the anti-apoptotic gene MCL1 transcripts as well as Bcl 2 in myeloid leukemias and such increase reflects poor prognosis (Li et al, 2019). In our study, no relationship was found between Mcl-1 expression and age, sex, TLC, PLT, BM blasts, cell surface antigens or FLT3-ITD.…”
Section: Discussionsupporting
confidence: 90%
“…However, El-Halawani et al, (2017) reported high level of miRNA29a expression in Flt3-ITD+ as compared to the Flt3-ITD. Moreover, the correlation analysis revealed the presence of significant positive direct association between levels of mir-29a and mir-92a (r=0.533, p = 0.001) and negative correlation with MCL1 transcript level was observed (r= -0.606, p<0.001, r= -0.339, p=0.043, respectively) and this was consistent with other studies that showed that down-regulation of miR-29a and miR-29b accompanied by up-regulation of the anti-apoptotic gene MCL1 transcripts as well as Bcl 2 in myeloid leukemias and such increase reflects poor prognosis (Li et al, 2019). In our study, no relationship was found between Mcl-1 expression and age, sex, TLC, PLT, BM blasts, cell surface antigens or FLT3-ITD.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with these findings, MCL-1 upregulation is frequently found at disease recurrence [ 127 ] and high levels of MCL-1 are linked to poor outcome. [ 128 ]. In contrast to this, mitochondrial priming measured by BH3 mimetic peptides showed primary AML cells from both refractory and sensitive patients responded more to the BAD BH3 peptide, which suggested a specific dependence on BCL-2 or BCL-w for these cells' survival.…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…The protein levels of Bcl-2 and Mcl-1 in various types of tumor tissues were found to be frequently augmented at a higher ratio than the other anti-apoptotic proteins in the Bcl-2 family [26]. In particular, increased expressions of Bcl-2 and Mcl-1 reflect a poor prognosis for many malignancies, including lung cancer [37][38][39]. Not only is their increased expression critical for oncogenesis and cancer progression, but these proteins are also involved in conferring chemotherapeutic drug resistance [35,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%